Authority of the Investigation Supervision Division in Case Resolution at Bali Police - Sihotang, Erikson; Wiranti Rendang, Dewa Ayu Sinta; Suryana , Kadek Dedy (Journal Of Social Science (JoSS), 2025)
This research is entitled "The Authority of the Investigation Supervision Division (Bagwassidik) in Case Resolution at the Special Criminal Investigation Directorate of the Bali Regional Police." The background of this study is based on the significant role of Bagwassidik in ensuring that the investigation process complies with the principles of criminal procedural law and the principles of fair and accountable justice. In practice, the investigation of special criminal cases often faces administrative and coordination issues, which affect the effectiveness of case resolution. This study aims to examine the implementation of Bagwassidik’s authority and the challenges faced in carrying out its supervisory function over investigations. The method used is normative juridical, employing statutory and conceptual approaches, supported by empirical data obtained through interviews with personnel from the Special Criminal Investigation Directorate of the Bali Regional Police. The data analysis techniques used are descriptive, evaluative, and argumentative. The results of the study indicate that Bagwassidik plays a strategic role through its supervision and evaluation functions during case presentations (gelar perkara). However, its implementation is hampered by vacant positions, limited personnel, weak coordination, and administrative issues such as incomplete documentation and sudden scheduling of case presentations. This research recommends the digitalization of administrative processes, strengthening institutional structures, and fostering a more collaborative culture to support the effectiveness of investigation supervision.